Indonesian traveler study: analyze the role of the big five personalities on hard adventure traveler type - Akhrani, Lusy Asa; Dewi, Chintya Fatima (Journal of Sustainable Tourism and Entrepreneurship, 2020)
Purpose: This study aims to determine the role of big five personalities simultaneously and partially towards the tendency of hard adventure travelers. Research methodology: This study will also look at the five traits found in the big five personalities which tend to play a role in the hard adventure traveler. This research is a replication study of Kristin Scott and John C. Mowen with a quantitative approach involving 1,558 subjects with a purposive sampling technique. Big five personality was measured using the big five infentory scale, while the hard adventure type would be measured using a scale from Scott & Mowen. Data analysis of this study using multiple regression techniques. Results: The results showed that there is a role of big five personalities that is simultaneous towards traveler's hard adventure type of 7,6%, whereas partially openness, extraversion, and neuroticism trait had a role towards the type of hard adventure, where openness trait had the biggest role towards hard adventure type. Limitations: Based on the magnitude of the role generated in this study, there are still other factors that can influence traveler's decision making to choose the traveling type, so that these other factors are expected to explore more. Contribution: This research can be a reference in the development of tourist attraction marketing by taking into account visitors' personality types.